Space in diachrony - Luraghi, Silvia, 1958-; Nikitina, Tatiana; Zanchi, Chiara (Studies in language companion series, 2017)
Space is a fundamental dimension of human life and is pervasive in human experience. Research on space has highlighted the possible asymmetrical nature of spatial relations. Differences in the encoding of goals and sources of motion are a case in point, and cross-linguistic coding tendencies show that path is less frequently flagged by a dedicated case than goal, source/origin, and (static) location (locative). Interestingly, such asymmetries may correlate with certain types of landmark, as in the case of toponyms or of animate entities. Even though these issues have been focused upon both in typological and psycholinguistic research, they remain largely open. The papers in this collection aim to show that a diachronic approach may shed light on the way in which asymmetries in the space domain come about over time, thus contributing to the clarification of synchronically puzzling facts.